Participación de la familia como coterapeuta en el síndrome de abstinencia por consumo de drogas psicoactivas - Landeta Lara, Danna Estefania (2018)
In the following work was developed based on a unique case of drug use in a state of abstinence where the participation of the family in the sector 5 corners of the city of Babahoyo, Province of Los Ríos, where the method was used exploratory in a first approach to the problem of study a superficial level of knowledge. Likewise, the clinical method was used when diagnosing the patient, following the corresponding steps the disease and its impact on the family, community and society in general are demonstrated, within the techniques the Semi-Structured interview, the direct observation, is evidenced that relied on the instruments of: format of questions, clinical history, test (Test of detection of alcohol consumption, tobacco and substances (ASSIST) Dr. Luis Alfonzo). After the case analysis and the intervention that was carried out; Valuation was obtained according to the ICD 10 International Classification of Diseases, Carlos presents withdrawal syndrome due to the use of psychoactive substances F1x.3. According to the exploration of the case, it can be noted that the family tries to work as a team to counteract Carlos' problems and is very aware of how he works at home and abroad, to avoid any risk factor I play Carlos’s recovery. It is proposed: a family therapeutic plan or program, which consists of being an integral and interdisciplinary approach to the patient, orienting it towards complete abstinence. With the idea of strengthening the team work of the members of the household and at the same time training parents to play the role of co-therapists, with appropriate strategies and aimed at improving their process of abandonment of substances; In this way, the rehabilitated will feel the inclusion of social and family type for his quick and successful recovery